Postnatal development of rats exposed to fluoxetine or venlafaxine during the third week of pregnancy - V.A. da-Silva (Brazilian Journal of Medical and Biological Research, 1999)
The aim of the present study was to compare the toxic effects of fluoxetine (F) (8 and 16 mg/kg) and venlafaxine (V) (40 and 80 mg/kg) administered during the third week of pregnancy on early development of rats. Both antidepressants were administered by gavage on pregnancy days 15 to 20 to groups of 10 to 12 animals each. Duration of gestation, food and water consumption, number of live pups and birth weight were recorded. Litters were culled to six pups at birth (day 1) and followed for growth until weaning (day 25). On day 60, a male and a female from each litter were injected with the 5-HT1 agonist, 5-methoxy-N,N-dimethyltryptamine (6 mg/kg, ip) and the serotonergic syndrome was graded. Fluoxetine but not venlafaxine reduced the duration of pregnancy when compared to the control (C) group (F = 21.1 days and C = 21.6 days, mean, P<0.02; maximum = 22 days and minimum = 21 days in both groups). The highest doses of both fluoxetine, 16 mg/kg (F16), and venlafaxine, 80 mg/kg (V80), reduced the food intake of pregnant rats, resulting in different rates of body weight gain during treatment (from pregnancy day 15 to day 20): F16 = 29.0 g, V80 = 28.7 g vs C = 39.5 g (median). Birth weight was influenced by treatment and sex (P<0.05; two-way ANOVA). Both doses of fluoxetine or venlafaxine reduced the body weight of litters; however, the body weight of litters from treated dams was equal to the weight of control litters by the time of weaning. At weaning there was no significant difference in weight between sexes. There was no difference among groups in number of live pups at birth, stillbirths, mortality during the lactation period or in the manifestation of serotonergic syndrome in adult rats. The occurrence of low birth weight among pups born to dams which did not show reduced food ingestion or reduction of body weight gain during treatment with lower doses of fluoxetine or venlafaxine suggests that these drugs may have a deleterious effect on prenatal development when administered during pregnancy. In addition, fluoxetine slightly but significantly affected the duration of pregnancy (about half a day), an effect not observed in the venlafaxine-treated groups.